PENGEMBANGAN PERANGKAT PEMBELAJARAN KIMIA ANALITIK MATERI KROMATOGRAFI BERORIENTASI INKUIRI TERBIMBING - Kurniasih, Dedeh; Rahayu, Hanum Mukti (Jurnal Pendidikan Matematika dan IPA, 2017)
The purpose of this research is to develop valid, practical, and effective guided inquiry teaching set to improve the students’ achievement on the course of Analytical Chemistry in Muhammadiyah University. The researcher applied Thiagarajan 3-D model; define, design, and develop. The sample of this research was obtained by purposive sampling resulted in 7 students as the try out sample and 16 students as the main test sample. The data was collected by measurement, and indirect observation. The instruments of this research were pre-test and post-test questions, observation sheets, and questionnaire sheets. The findings of this research showed that the validity of the teaching set was given the score 1,00 by expert; the practicality of the teaching set from the students’ responses was given the score 75,60 and 82,46; the students’ achievement after utilizing the guided inquiry based teaching set showed that 81,25% fulfill the criteria of completeness. For that reason, the guided inquiry based teaching set developed in this research is suitable to be used in the teaching and learning process. Keywords: Guided inquiry, chromatography, the development of a teaching set